ANALISIS SIFAT FISIS PADA RESERVOAR BATUPASIR MENGGUNAKAN METODE SEISMIK INVERSI IMPEDANSI AKUSTIK (AI) DAN MULTIATRIBUT PADA LAPANGAN “MNF” CEKUNGAN BONAPARTE - Muhammad Niko Febridon; Bagus Sapto Mulyatno; Egie Wijaksono (Jurnal Geofisika Eksplorasi, 2018)
Analysis of the physical properties of the sandstone reservoir in this study was carried out using the acoustic impedance inversion method and seismic multi-attribute which was carried out at the Bonaparte Basin "MNF" Field. In this study, the acoustic impedance distribution is generated, and the acoustic impedance is derived to obtain a water saturation distribution map and the volume of the log property is predicted to predict pseudo gamma ray, density and porosity with multi-attribute analysis using linear regression method with step wise regression technique. From the results of well data crossplot analysis for sand-shale sensitivity analysis and inversion analysis on sandstones filled with hydrocarbon fluid obtained the acoustic impedance value is between 12,000 ft / s * g / cc - 27,000 ft / s*g / cc. In the Middle part around the NN-1, NN-3 and NN4 wells and the Southeastern part of the research area are prospect areas that have gamma ray values with a range of 5-70 API, density with a range of 2.1-2.3 gr / cc and porosity with a range of 18-23% and SW of 10-13% indicating that the hydrocarbon gas accumulated in the research field. The results of the multi-attributes and acoustic impedance show that the sandstones in this field are thight sandstones.